2022
DOI: 10.3390/v14102082
|View full text |Cite
|
Sign up to set email alerts
|

Genomics, Transcriptomics, and Proteomics of SSV1 and Related Fusellovirus: A Minireview

Abstract: Saccharolobus spindle-shaped virus 1 (SSV1) was one of the first viruses identified in the archaeal kingdom. Originally isolated from a Japanese species of Saccharolobus back in 1984, it has been extensively used as a model system for genomic, transcriptomic, and proteomic studies, as well as to unveil the molecular mechanisms governing the host–virus interaction. The purpose of this mini review is to supply a compendium of four decades of research on the SSV1 virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 89 publications
(205 reference statements)
0
3
0
Order By: Relevance
“…The lemon(spindle) viral morphotype is unique to the domain archaea and is the most abundant particle shape in several hyper-saline ecosystems 27,28 . Surprisingly, LSV-48N is unrelated to previously isolated haloarchaeal lemon-shaped viruses 17,18 , but rather shares several characteristics with fuselloviruses of Thermoproteota (such as SSV1 and SSV2), despite lack of significant sequence similarity, having a circular double stranded genome, causing no cell lysis, and existing both as circular plasmid-like form and as an integrated provirus 21,29 . Furthermore, infection by SSV1 was shown to dampen the induction of CRISPR-Cas systems in Saccharolobus solfataricus similar to what we show for LSV-48N 30 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The lemon(spindle) viral morphotype is unique to the domain archaea and is the most abundant particle shape in several hyper-saline ecosystems 27,28 . Surprisingly, LSV-48N is unrelated to previously isolated haloarchaeal lemon-shaped viruses 17,18 , but rather shares several characteristics with fuselloviruses of Thermoproteota (such as SSV1 and SSV2), despite lack of significant sequence similarity, having a circular double stranded genome, causing no cell lysis, and existing both as circular plasmid-like form and as an integrated provirus 21,29 . Furthermore, infection by SSV1 was shown to dampen the induction of CRISPR-Cas systems in Saccharolobus solfataricus similar to what we show for LSV-48N 30 .…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, infection by SSV1 was shown to dampen the induction of CRISPR-Cas systems in Saccharolobus solfataricus similar to what we show for LSV-48N 30 . However, unlike SSV1 that has a “harmonic coexistence” with its host, with only minor effects on host gene expression (unless induced by UV), and little effect on growth 21,29 , LSV-48N causes drastic changes in both host gene expression and growth.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Fusellovirus, previous studies in Los Azufres reported the presence of viral sequences related to this group that infect archaea, and it is believed that this group has a key role in the gene exchange between archaea populations. As well, the presence of these viruses is common in geothermal environments [50].…”
Section: Discussionmentioning
confidence: 99%